ТHE SOCIO - POLITICAL CONDITIONS AND ENTREPRENEURSHIP IN THE REPUBLIC OF MACEDONIA - Mijalov, Risto; Iliev, Dejan; Kitevski, Goran (Faculty of Economics, University of Banja Luka, 2014)
The transformation of the Republic of Macedonia to an open market society, through the years of independence is accompanied by a series events and occurrences that are characterized as social and political problems and processes. Overall, the frequency and intensity of events of general social nature is such that Macedonia has acquired the image of a country that is categorized into social and political incoherent countries. It is not in the favor of the strong will of the Republic of Macedonia and the striving for greater economic liberalization, establishment of macro and micro economic conditions that create favorable business climate, and more. From one perspective, it is the social and political situations that create Macedonian openness on economic participation and entrepreneurship, and on the other hand, such problems and processes are blocking the creation of the “economic oasis“ in the region. Concrete terms and occurrences that are classified as social and political developments and difficulties will be explained in the paper, as well as the tendency of the state to establishment the entrepreneurship of highest order.
Keywords: entrepreneurship, society, liberalization, business problems